Health Needs Assessment methodology report in blind veterans 2007 - R. Amini (Afarand Scholarly Publishing Institute, 2009)
Every population have to change programs and resources to develop health services. Health needs assessment as a method can be used in planning process for health service programs. Health needs assessment has many steps which the first one is population profile definition. Health level assessment method should be chose at the next stage. Depending on the method of health level assessment, data gathering process will be clarified and also data gathering instruments. Following data analysis, priority setting is the next step, which prepares input of planning. This report describes the research method of health needs assessment in Iranian blind veterans in 2007. Sampling, data gathering, response rate, priority setting and discussion are the main parts of the report. There was no précised and reliable information about the blind veterans, so that no body could plan for their health services. General health, musculoskeletal and psychiatric assessment accompanied by attitude survey was the main aims of the study. Following many expert panels, using deep interview techniques, data gathering instrument prepared. The validity and reliability of the instruments were evaluated in a pilot study on 30 blind veterans. The last edition of instruments and data sheets was revised by expert panels. Data gathering for population profile definition and needs assessment took place in 10 days, when 60% of total population were in a camp. Statistical analysis out put, and the results of literature review were discussed in expert panel. Priority setting of the health needs was the last phase of the study which came out of expert panel using focus group discussion method. Cardiovascular attack risk factors, paranoid thinking, planning for leisure, diabetes control and depression were the first five priorities.